Evaluation of the Inhibitory Effect of Moringa oleifera Leaves Methanolic Extract against In Vitro Growth of Several Babesia Species and Theileria equi and the In Vivo Growth of Babesia microti - Mohamed Abdo Rizk; Shimaa Abd El-Salam El-Sayed; Mohamed Z. Sayed-Ahmed; Yosif Almoshari; Saad S. Alqahtani; Sarfaraz Ahmad; Nawazish Alam; Basma H. Marghani; Abdelbaset E. Abdelbaset; Ikuo Igarashi (Journal of Tropical Medicine)
The current study evaluated the inhibitory effect of Moringa oleifera leaves methanolic extract (MOL) against the in vitro growth of Babesia bovis (B. bovis), B. caballi, B. bigemina, and Theileria equi (T. equi), as well as in vivo growth of B. microti in mice. Active principles of MOL extract were determined using liquid chromatography mass spectrometry (LC-MS). MOL’s anti-piroplasm efficacy was assessed both in vitro and in vivo using the SYBR Green I fluorescence assay. Every 96 hours, the hematological parameters, including red blood cell count (RBCs; 104/UL), hemoglobin content (HGB; g/dl), and hematocrit percent (HCT; %), in the treated mice were monitored using a Celltac MEK6450 automated hematological analyzer. LC-MS of MOL revealed that the most abundant polyphenolic catechism found in the MOL extract was isoquercetin and rutin. MOL inhibited B. bovis, B. caballi, B. bigemina, and T. equi in vitro growth in a dose-dependent way, with IC50 values of 45.29 ± 6.14, 19.16 ± 0.45, 137.49 ± 16.07, and 9.29 ± 0.014 μg/ml, respectively. MOL’s in vitro antibabesial activity was enhanced when administrated simultaneously with either diminazene aceturate (DA) or MMV665875 compound from malaria box. In mice infected by B. microti, a combination of MOL and a low dose of DA (12.5 mg·kg−1) resulted in a significant (P<0.05) reduction in B. microti growth. These findings suggest that MOL is an effective herbal anti-piroplasm therapy, especially when combined with a low dosage of either DA or MMV665875.